Formative research to characterize retail food environments in northern Tanzania: FRESH Field Notes - De Bruyn, J.; Marshall, Quinn; Kumar, Neha (International Food Policy Research Institute, 2023)
Fruits and vegetables are critical to a healthy diet. In many parts of the world, their consumption remains far below recommended levels. To help understand how to support greater intake of fruit and vegetables, researchers in the CGIAR Research Initiative on Fruit and Vegetables for Sustainable, Healthy Diets (FRESH) are exploring ways to understand, categorize, and evaluate the spaces where people make decisions about acquiring and consuming food—known as food environments. As part of a formative information-gathering process, researchers carried out field visits to study sites in Arusha and Kilimanjaro Regions in northern Tanzania, to revise and refine a food vendor typology, a list of foods commonly available in the study area, and descriptions of other food environment features. Information gathered has been used to inform research design decisions and questionnaire development for an upcoming evaluation study.